2019
DOI: 10.1097/pgp.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Profile in Vulvar, Vaginal, and Urethral Melanomas: Review of 37 Cases With Focus on Primary Tumor Site

Abstract: Melanomas of female genital tract are rare tumors with poor prognosis. While BRAF-V600E is the most common pathogenic mutation seen in cutaneous sun-exposed melanomas, mucosal and anogenital melanomas usually lack BRAF mutations and instead they harbor KIT alterations. The American Joint Committee on Cancer staging guideline (AJCC eighth edition) recommends using cutaneous melanoma guidelines for vulvar melanoma staging and does not provide any recommendations for vaginal melanoma staging. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…PS-PLA1, the sole substrate of LysoPS, is detectable across several physiological states and is restricted to the inner surface of cellular membranes, apoptotic cells, antigen-activated lymphocytes, and immunological escape of melanoma cells [69] . It is clear that the cause of MM is mostly associated with mutagenesis, with the involvement of several oncogenes, including BRAF and NRAS [70] . It is possible that PLA1A , with the highest sensitivity, specificity, and AUC, could be used as a single indispensable biomarker for the diagnosis, screening, and prognosis of BRAF mutation melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…PS-PLA1, the sole substrate of LysoPS, is detectable across several physiological states and is restricted to the inner surface of cellular membranes, apoptotic cells, antigen-activated lymphocytes, and immunological escape of melanoma cells [69] . It is clear that the cause of MM is mostly associated with mutagenesis, with the involvement of several oncogenes, including BRAF and NRAS [70] . It is possible that PLA1A , with the highest sensitivity, specificity, and AUC, could be used as a single indispensable biomarker for the diagnosis, screening, and prognosis of BRAF mutation melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Omholt et al reported eight c-KIT mutations in 23 women with VM vs no mutations in seven women with vaginal melanomas [ 24 ]. No difference in the mutational profile between the hair-bearing and glabrous skin of the vulva appears to be present [ 25 ]. KIT activates downstream signaling cascades of the Ras/Raf/MEK/ERK pathway, a key regulator of melanoma cell regulation [ 26 ].…”
Section: Cancerogenesis and Molecular Biology Of Vmmentioning
confidence: 99%
“…Vulvar melanoma can arise from the hairy or from the glabrous part of the vulva. The significance of tumor location, although controversial, 4 could account for the particular behavior and the molecular characteristics of this disease that make it a distinct entity from cutaneous and other mucosal melanomas. 5 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Vulvar melanoma can arise from the hairy or from the glabrous part of the vulva. The significance of tumor location, although controversial, 4 could account for the particular behavior and the molecular characteristics of this disease that make it a distinct entity from cutaneous and other mucosal melanomas. 5 In the metastatic disease, survival is usually poor, due either to the aggressive biological behavior or to the lack of efficacy of novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation